Isolation and utilization of tobacco-based cellulose nanofiber (TCNF) for high performance reconstructed tobacco sheet (RTS). (1st June 2021) - Luo, Boya; An, Xingye; Yang, Jian; Liu, Liqin; Zhang, Hao; Hu, Qin; Zhang, Runqing; Nie, Shuangxi; Wu, Shijie; Cao, Haibing; Cheng, Zhengbai; Liu, Hongbin
Graphical abstract: Highlights: Tobacco stem waste was applied to isolate cellulose nanofibers with unique properties. A feasible pretreatment combined with mechanical method was applied for TCNF isolation. TCNF can be utilized in the preparation of RTS for improved mechanical performance. The addition of TCNF can effectively reduce the proportion of wood pulp in RTS. Abstract: Nowadays, wood pulp addition (such as softwood, hardwood, etc.) into manufacture reconstructed tobacco sheet (RTS) via a paper-making process is a feasible and sustainable technology. However, the addition of wood pulp in RTS would weaken the tobacco fragrance of cigarette by bring wood gas when smoking. In this study, a practical and feasible pretreatment by hot water/cooking process combined with cationic modification/homogenization treatment was proposed to directly isolate desirable cellulose nanofibers from tobacco stem, named TCNF. The obtained TCNF was applied in the preparation of RTS to improve its physical properties but with a reduced wood pulp proportion (from 25 wt% decreased to 16 wt%). Results showed that TCNF exhibit a similar morphology with wood based nanocellulose, and that the addition of TCNF (0.5 wt% based dried tobacco pulp) can substitute 9 % of wood pulp compared with that of the control at the similar physical properties.